TEACHER OF THE 21ST CENTURY - Ramilievna, Gridneva Rufina (PT. Antis International Publisher, 2024)
the publication was prepared based on the results of PISA 2022, an analysis of the success of leading countries. What competencies do teachers in these countries have, and do they inspire their students with this? requirements for a teacher of the 21st century.